PENGARUH KUALITAS PRODUK DAN SUASANA TERHADAP KEPUTUSAN PEMBELIAN MELALUI CITRA MEREK PADA KOPI NAKO SUMMARECON BEKASI - elvina octaviana; Bonifasius MH Nainggolan (LPPM and Travel Operation Department Universitas Asa Indonesia, 2023)
The objective of this study is to examine the impact of product quality and atmosphere on consumers' purchasing decisions through brand image. Data collection by distributing questionnaires to 220 respondents at Kopi Nako Summarecon Bekasi. Incidental sampling is used as a sampling method and is processed using the SmartPLS 2.3 application. The results of this study indicate that product quality has a significant effect on brand image, product quality has a significant effect on purchasing decisions, atmosphere has a significant effect on brand image, atmosphere has no significant effect on purchasing decisions, brand image has a significant effect on purchasing decisions and for indirect influence. There is an indirect effect of product quality on brand decisions mediated by brand image, there is an indirect effect of atmosphere on purchasing decisions mediated by brand image.